Evaluation criteria for competency-based syllabi: a Chilean case study applying mixed methods. Issue 4 (18th May 2016) - Jerez, Oscar; Valenzuela, Leslier; Pizarro, Veronica; Hasbun, Beatriz; Valenzuela, Gabriela; Orsini, Cesar
Abstract: In recent decades, higher education institutions worldwide have been moving from knowledge-based to competence-based curricula. One of the greatest challenges in this transition is the difficulty in changing the knowledge-oriented practices of teachers. This study evaluates the consistency between syllabus design and the requirements imposed by a competence-based learning environment. To make this comparison, the study sets four criteria (C1: explicit relationship between syllabus and graduate profile; C2: precision of the learning outcomes and assessment criteria; C3: contents that mobilise the learning outcomes; and C4: learning and assessment activities) derived from the literature and a thematic analysis of competence-based learning in higher education. Afterwards, a sample of 150 syllabi from different disciplines of five Chilean public universities were analysed, all of which stated the use of learning outcomes and competences in their learning models. Using a three-point Likert scale derived from the aforementioned criteria and their indicators, a comparison was made between the actual practices reflected in the syllabus design and the previously established criteria. Results show a gap between the declaration of a competency-based curriculum and actual syllabus outlines. Moreover, there are important differences among disciplines. Although all disciplines present high levels of accomplishment for Criteria 1 and 3, only the discipline of health sciences presents an acceptable level for Criteria 2 and 4. It is recommended that further research be undertaken towards identifying effective competency-based syllabus design.